Effect of hormone administration during peripartum period in crossbred sows - SNEH,; SINHA, A K; SINGH, BALRAJ; SINGH, S K (The Indian Journal of Animal Reproduction, 2003)
Efficacy of PGFp and/ or oxytoqn was evaluated in four groups of sows (n=80) PGF 2a 5mg I/ mon day 111 (group I), PG on day 111 and oxytocin20 IU 1/m after the birth offirstpiglet (group II), PGafter the birth of first piglet (group III) and oxytocin after the birth of first piglet (group IV) along withsuitable controls (group V and VI). The induction interval ranged from 26.85±0.52 to 28.16± 0.43hours in group I and II, respectively. Duration of second stage of farrowing in all the four treatmentgroups was less than three hours, whereas, it was more than four and half hours in control groups.The overall piglet interval in this study varied from 6.57±0.41 to 7.92±0.92 minutes.
Keywords: parturition induction; sows; PGE2alpha; oxytocin; lutalyse; farrowing duration; piglet interval